Address Terms In English And Konjonese: A Sociolinguistic Study - Ahmad Rizal Abdullah; Fitriansal Fitriansal (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
This research aimed to 1) identify the the address terms existing in English and Konjonese, and 2) to analyze the aspects affecting the use of the address terms in English and Konjonese. this research used a descriptive and qualitative approach. Qualitative as research procedure produces descriptive data involving oral and written data from people and behavior that can be observed. The data is taken by Recording the conversation which is done by people from Konjo community. The recording is taken by using smart phone’s recorder in various circumstances such as in family gathering, office and neighborhood situations. the result of the research is that there is a different between the use of the address terms in English and Konjonese. In English, the speakers sometimes used the first name of the addressee to show the closeness while in Konjo dialect, there are particular title used to address someone particularly those who are older. In addition, there several aspects affecting the use of the address terms involving situation, age different and social distance as well as social status.